Analysis of Yields and Profitability of Utilizing Blended Soybean Seed in Kansas - Newlin, Dustin (My University, 2020)
Kansas farmers must continue to find ways to alleviate risk and increase profits, especially in a challenging agriculture economy. This study analyzes the economic feasibility of blending two different soybean seed varieties together to create a blended variety of soybean seed. Utilizing eight years of plot data (2012-2019) across fifteen plot locations in Kansas, an analysis is conducted comparing blended soybean seed varieties to single soybean seed varieties. A single-factor analysis of variance is used to analyze the difference in yields between blended soybean varieties and single soybean varieties. A partial budget analysis is used to evaluate economic feasibility. Results show two years, 2012 and 2013, having statistical significance in yield difference, with higher yields for blended varieties. Results of analysis by location show six out of fifteen locations having statistical significance, with higher yields by blending soybean varieties. An overall analysis of the combined data set shows a 4.68 bushel per acre yield advantage by blending soybean seed varieties. A partial budget analysis shows an increase in net revenue per acre of $30.14, using a $10 cost premium on blended soybean seed varieties.
Keywords: Blended Soybeans; ANOVA; Profitability; Agriculture; Economics; Yield